¿cuál es el mejor fertilizante para una pradera de marandu y xaraes en el corto plazo? - Vilela de Rezende, Adauton; Silveira Rabêlo, Flávio Henrique; dos Santos, Rafael Tadeu; González-Villalba, Hugo Abelardo; Silveira Rabelo, Carlos Henrique [UNESP]; Rodrigues, Marcos (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2017)
Several fertilizers with different efficiency and price are commercially available to increase the yield of pastures, generating doubts about which should be chosen for fertilization, especially regarding short term operation returns. Our objective was to investigate the effect of simple and compound fertilizers on the production, chemical composition and economic parameters of Marandu and Xaraes palisade grass in the short term. The fertilizers Urea, Super N, 08-28-16, 30-00-20 and 20-10-10 were evaluated in three cuts of the pasture. The overall rate of tiller occurrence, dry matter production, crude protein content, total digestible nutrients and digestible energy of Marandu palisade grass increased with the supply of nitrogenous fertilizers, while neutral detergent fiber (NDF), acid detergent fiber and hemicellulose content decreased. Fertilization using Super N resulted in higher production of mass per kilogram of fertilizer applied and per unit of real (R$) invested per hectare. The number of tillers of Xaraes palisade grass increased and NDF content decreased with the application of 20-10-10. Fertilization of Marandu palisade grass with Super N is more efficient from the economic and productive point of view than fertilization with urea. Comparing the grasses, Xaraes is more demanding in phosphorus and potassium than Marandu.
What is the best fertilizer for marandu and xaraes palisadegrass production in the short term?
Keywords: Chemical composition; Morphological characteristics; Production cost